Pengaruh Audit Internal Dan Sistem Informasi Akuntansi Dalam Menunjang Efektivitas Pengendalian Internal: Studi Kasus Pada Inspektorat Kabupaten Aceh Barat - Dina Asmita; Lilis Marlina (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
Internal control plays a crucial role in supporting the achievement of an organization's goals. In general, internal control provides significant benefits in securing organizational assets, improving the reliability and accuracy of financial and operational information, and ensuring compliance with applicable policies, regulations, and laws. With effective internal control, an organization can protect its resources from the risk of misuse, fraud, or waste. This research is a quantitative study using multiple regression analysis. The population in this study was all 80 employees of the West Aceh Inspectorate. The number of samples used was calculated using the Slovin formula and random sampling technique, resulting in 45 people as research samples. The quantitative analysis in this study was conducted using the Statistical Product and Service Solution (SPSS) version 26 computer program, which allows for rapid analysis and produces more accurate output. The results of the study indicate that internal audit has a partial significant influence on the effectiveness of internal control at the West Aceh Inspectorate. In addition, the accounting information system also has a partial significant influence on the effectiveness of internal control at the West Aceh Inspectorate. Overall, both internal audit and accounting information systems significantly influence the effectiveness of internal control at the West Aceh Inspectorate. This study underscores the importance of both factors in supporting the achievement of organizational goals and better resource management. Overall, both internal audit and accounting information systems significantly influence the effectiveness of internal control at the West Aceh Inspectorate. This study underscores the importance of both factors in supporting the achievement of organizational goals and more effective and efficient resource management.